MENILAI KINERJA KEUANGAN MASKAPAI PENERBANGAN GARUDA INDONESIA DI SAAT PANDEMI COVID-19: STUDI KASUS - Diana Tambunan; Tri Widyastuti (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to analyze the financial performance of Garuda Indonesia Airline during the pandemic COVID-19. The research methodology is a comprehensive analysis of the Garuda Indonesia’s financial statements and annual reports listed at Indonesian Stock Exchange. The financial statements were analyzed to evaluate the financial performance and to assess the severity level of the COVID-19 pandemic impact on corporate income and profit. The findings of this study showed the deteriorating of the liquidity, solvency and profitability positions after the emergence of the COVID-19 pandemic. The findings from aggregate analysis of financial performance showed that in 2020 the corporate lost USD2.48 bilions and the current liabilities exceeded its current assets as much as USD3.8 billions. Garuda Indonesia experienced negative equities of USD1.9 billions, and requires operational strategies such as cost efficiency, debt restructuring and good corporate governance in order to pay its debts on creditors, lessors and vendors. The practical implications are an increase in understanding of financial performance, allowing the corporate managers to improve their financial managements, and adopting the right strategy in overcoming its financial difficulties during the COVID-19 pandemic